Bovine Digesta as Organic Fertilizer in Gliricidia Fodder Banks: Agronomic Responses and Nutrient Composition - Silva, P. H. F.; Medeiros, G. R.; Santos, S. G. G. C.; Cavalcante, I. T. R.; Neves, R. S.; Carvalho, C. B. M.; Costa, J. H. S.; Sales-Silva, T. B.; Rigueira, J. P. S. (Tropical Animal Science Journal, 2025)
Bovine digesta is an innovative by-product from slaughterhouses to fertilize forage crops, but applying excessive amounts can be inefficient in terms of dry matter yield (DMY) and nutritional characteristics. A two-year trial, which encompassed two rainy and two dry seasons, was conducted to assess the agronomic responses and nutrient composition of gliricidia fertilized with increasing levels of slaughterhouse bovine digesta (0, 1.25, 3.12, 6.25, 9.37, and 12.50 t/ha). Gliricidia DMY enhanced linearly from 8.0 to 15.9 t/ha/yr of DM as the bovine digesta dosage increased from 0 to 12.50 t/ha (p=0.0003). The DMY stability variance increased from 0 (σi2 = 0.10) to 12.50 t/ha (σi2 =14.09), so the bovine digesta reduced the DMY stability. Plant height also responded linearly to the fertilizer levels (p<0.0001). Consistent gains in leaf crude protein concentration (21.8, 22.5, 23.0, 23.7, 24.4, and 24.9 % DM for 0.00, 1.25, 3.12, 6.25, 9.37 and 12.50 t/ha, respectively) were observed because of the fertilizer levels (p<0.0001). As the gliricidia responds linearly to the bovine digesta fertilization regarding important agronomic and nutrient-composition traits, we recommend applying the top required dose (12.50 t/ha) to combine maximum forage yield and great roughage nutrient composition. It is not worth saving the organic fertilizer by using lower dosages.